Do individual investors trade differently in different markets? - Abreu, Margarida (2018)
We investigate the hypothesis that the same investors trade differently in different financial markets. We use a proprietary data base with the transaction records of 129,461 investors for a 10-year period, and select the investors holding both stocks and warrants in the port-folio. We compare the trading behavior of investors in the stock market and in the warrant market, controlling for investors’ socio-demographic characteristics (age, occupation, edu-cation, etc.) and for investors’ behavioral biases (overconfidence, the disposition effect and pursuit of the pleasure of gambling). Even though investors are the same in both markets, our results clearly show that the soci-odemographic determinants of the trading activity in stocks and in warrants are not all the same, implying that the same investors trade stocks differently than warrants. More pre-cisely, overconfident investors have a higher warrant trading activity and a lower domestic stock trading activity, and investors pursuing gambling pleasure or prone to the disposition effect trade warrants more (but do not trade stocks more).